Heritable priming by Trichoderma: A sustainable approach for wheat protection against Bipolaris sorokiniana - Tiwari, Menka; Singh, Rajat; Jha, Rintu; Singh, Prashant (Frontiers in Plant Science, 2022)
Crop plants encounter a variety of biotic challenges in the field and faces significant reduction in crop yield. In the current scenario of an ever increasing global population, there is an urgent need to protect plant health by using sustainable approach to maximize the crop productivity and to mitigate the food demands. Nowadays, we mostly rely on chemical crop protection techniques, which are causing a number of environmental and health difficulties. Defence priming is a chemical-free, eco-friendly, and sustainable strategy of crop protection, which is also called “green vaccination. In the present study, for the first time, we used Trichoderma as a priming agent to protect wheat crop from spot blotch disease. We have established Trichoderma-mediated defence priming in wheat against Bipolaris sorokiniana for sustainable crop improvement. We have characterised the morphological, disease phenotype, biochemical and yield parameters of Trichoderma-primed and non-primed wheat under disease pressure. Trichoderma-primed plants were found to be more protected against B. sorokiniana as compared to non-primed plants. Biochemical studies indicated that there is no direct defence response after priming stimulus but the defence response was activated only after triggering stimulus in terms of enhanced defence metabolites in primed plants as compared to non-primed plants. In the present study, since defence was activated only when required, that is under disease pressure, there was no unnecessary allocation of resources towards defence. Hence, no yield penalty was shown in primed plants as compared to control. We further evaluated the inheritance of primed state to the next generation and found that progeny of primed parents also performed better than progeny of non-primed parents under disease pressure in terms of protection from B. sorokiniana as well as yield performance. This strategy has the potential to protect crop without any yield penalty and causing environmental degradation. Our research findings indicate that Trichoderma-mediated defence priming could be an alternative approach for improving wheat productivity under biotic stress. To be our best knowledge, this is the first documented report for the Trichoderma-mediated defence priming and induced inheritance in wheat plant. This study will open new arenas in sustainable crop protection strategies for the exploitation of defence priming in crop plants.